Emergency pharmacy workforce views and experience related to the provision of pharmaceutical care during mass gathering events: the FIFA World Cup Qatar 2022™ experience - Naseralallah, Lina; Isleem, Nour; Aboelbaha, Shimaa; Pallivalapila, Abdulrouf; Alnaimi, Shaikha; Al Hail, Moza (Frontiers in Public Health, 2023)
This study aimed to explore emergency pharmacy workforce perspectives and experiences in providing pharmaceutical care during mass gathering events (i.e. FIFA World Cup Qatar 2022™).Methods: A qualitative methodology was employed using focus groups discussions. Emergency pharmacists across Hamad Medical Corporation were invited to participate using a combination of purposive and snowball sampling.Focus groups were audio-recorded, transcribed verbatim, and validated. Inductive thematic analysis was undertaken to generate key themes and subthemes.Results: Four focus groups were conducted which included 21 participants and generated five major themes. Whilst participants had mixed opinions in relation to their preparedness to practice during the World Cup, they perceived their experience as successful and smooth. The primary perceived facilitators were management support, mobile medical units, and high public health awareness. The main highlighted barriers were related to staff insufficiency, medications availability, and cultural and language challenges. Participants recommended pharmacist's role identification in mass gatherings, development of pharmacy action plan, and offering simulation training and pharmacy-specific training. Conclusion: Despite the perceived barriers, pharmacists reported positive views in relation to their experience in providing pharmaceutical care during mass gatherings. Future research should focus on the development of theorydriven action framework for pharmacy departments to adopt during mass gatherings.